RATIONALIZATION OF DIVISION OF DOMESTIC WORK AMONG YOUNG MIDDLE-CLASS FAMILIES - Diah Mutiara Johar; Siti Mas'udah (Jurnal Sosiologi Nusantara, 2022)
The discourse on gender equality in society is growing. Although the participation of women working in the public sector is increasing, the roles of husband and wife are still divided sexually. Domestic work and child care are still the primary responsibilities of women. This study examines gender inequality and the rationalization of the work division in young couples’ households in urban communities. This study uses a qualitative method. This study uses the theory of doing gender and symbolic interactionism. This study found that families with an unequal division of domestic work made rationalization of gender inequality within the family. Various excuses were given to disguise the unequal division of domestic work between husband and wife. This happens because of the patriarchal ideology in Javanese society. The wife was given more responsibility for domestic work and child care than the husband. In traditional families, inequality in the division of domestic work is rationalized for the following reasons, namely gender, standards, and time. In transitional families, inequality in domestic work is rationalized through gender, standards, skills, time, religion, and avoiding conflict. In an egalitarian family, family members do domestic work based on their responsibilities and initiatives. The actors who perpetuate gender inequality in young families are husbands, husbands and wives, and extended family members. This study concludes that gender roles in young couples’ households are still traditional and perpetuated through rationalizing gender inequality in domestic work and childcare allocation.Keywords : Domestic Works, Family, Gender Equality, Gender Injustice, Women